Effect of using nanofluids and providing vacuum on the yield of corrugated wick solar still. (October 2015) - Omara, Z.M.; Kabeel, A.E.; Essa, F.A.
Highlights: Modified corrugated wick solar still integrated with an external condenser and used nanofluids. Effect of using different types of nanomaterials on the distillate water productivity. Effect of using various water depths with operating the vacuum fan on the distillate yield. Abstract: Purifying water using solar energy is a suitable green technique for rejecting salts from saline water. Solar stills are famous and simple devices for sea water desalination but their productivity from freshwater is limited. Various novel techniques were advanced and established to increase the solar still output yield. In the current work, experimental studies with modifications on the ordinary solar still have been conducted to investigate the performance of the new erected solar still. A hybrid solar distillation system comprising of corrugated and wick absorbers of solar stills is integrated with an external condenser to examine their performance. The first solar still is a base traditional type (CSS), while the other one is a corrugated wick still (CrWSS). The performance of CrWSS with internal reflectors, integrated with external condenser and using different types of nanomaterials is investigated and compared with the conventional still. The two types of solar stills are subjected to the same metallurgical conditions. The influence of saline water depth (1, 2, and 3 cm) on CrWSS performance was also investigated. Results showed that integrating an external condenser, with corrugated wick still, with reflectors improves the productivity of the modified solar still. Also; the yield of CrWSS with reflectors when providing a vacuum was enhanced to about 180% higher than the CSS. The productivity of the system is enhanced when using cuprous and aluminum oxides nano particles by an approximate percentages of 285.10% and 254.88% respectively.